Measuring Blended Learning Acceptance: Integrative Learning And Utaut Models (International Journal of Environmental Sciences, 2025)
Purpose – This look at investigates the acceptance of blended learning among students with the aid of using the Integrative Learning Design Framework and the Unified principle of acceptance and Use of generation (UTAUT) model. As educational establishments more and more adopt blended learning of tactics and information the elements influencing scholar acceptance are critical for a successful implementation. These research objectives are to evaluate the effectiveness of those fashions in measuring attractiveness tiers and discover key determinants of adoption.Methodology – A combined-methods technique was utilized, related to surveys and interviews with college students from numerous educational backgrounds. The UTAUT-primarily based questionnaire assessed factors inclusive of overall performance expectancy, attempt expectancy, and social impact on, and facilitating conditions. The information was analyzed the usage of statistical techniques to decide the connection between these factors and attractiveness ranges.Findings – The findings indicate that overall performance expectancies and social impact appreciably effect students' attractiveness of mixed mastering. The Integrative Learning of the Design Framework provided precious insights into the contextual factors influencing adoption. They have a look at and conclude that each fashions efficaciously investigate blended learning acceptance and provides hints for educators to enhance pupil engagement in blended learning environments.Significance – enhancing instructional results: with the aid of knowledge of the elements influencing scholar acceptance of bleanded learning, educators and establishments can tailor their processes to maximize engagement and improve learning consequences.